Endothelial podosome rosettes regulate vascular branching in tumour angiogenesis - Seano, Giorgio (Nat Cell Biol, 2014)
The mechanism by which angiogenic endothelial cells break the physical barrier of the vascular basement membrane and consequently sprout to form new vessels in mature tissues is unclear. Here, we show that the angiogenic endothelium is characterized by the presence of functional podosome rosettes. These extracellular-matrix-degrading and adhesive structures are precursors of de novo branching points and represent a key feature in the formation of new blood vessels. VEGF-A stimulation induces the formation of endothelial podosome rosettes by upregulating integrin α(6)β(1). In contrast, the binding of α(6)β(1) integrin to the laminin of the vascular basement membrane impairs the formation of podosome rosettes by restricting α(6)β(1) integrin to focal adhesions and hampering its translocation to podosomes. Using an ex vivo sprouting angiogenesis assay, transgenic and knockout mouse models and human tumour sample analysis, we provide evidence that endothelial podosome rosettes control blood vessel branching and are critical regulators of pathological angiogenesis.